2018
DOI: 10.1177/1045389x18806401
|View full text |Cite
|
Sign up to set email alerts
|

Bio-inspired self-healing cementitious mortar using Bacillus subtilis immobilized on nano-/micro-additives

Abstract: Bio-inspired self-healing strategies are much innovative and potentially viable for the production of healable cement mortar matrix. The present research explores the feasibility of gram-positive ''Bacillus subtilis'' microorganisms in the effective healing of nano-/micro-scale-induced structural and non-structural cracks. The main concern related to the survival of such microorganisms in cementitious environment has been successfully addressed by devising proficient immobilization scheme coherently. The inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Similarly, 9%, 7% and 2% increment was recorded in the case of C. amylolyticum (3A), C. imtechense (4F) and C. efficiens (1E) respectively. The strength improvement mechanism is associated with the pore refinement via calcite precipitation (Khushnood, et al, 2018). In vitro results of calcite precipitation (Fig.…”
Section: Mechanical Evaluation Of Cementitious Systemmentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, 9%, 7% and 2% increment was recorded in the case of C. amylolyticum (3A), C. imtechense (4F) and C. efficiens (1E) respectively. The strength improvement mechanism is associated with the pore refinement via calcite precipitation (Khushnood, et al, 2018). In vitro results of calcite precipitation (Fig.…”
Section: Mechanical Evaluation Of Cementitious Systemmentioning
confidence: 98%
“…The Bacillus species have been reported with maximum of 25.93% increase in compressive strength of cementitious mortar (Ghatiya and Pendharkar, 2017). Bacillus species are extensively researched in self-healing concrete; however, isolated strains in the recent studies have not been reported yet (Khushnood et al, 2018;Khushnood et al, 2019;Shaheen et al, 2019). Arthrobacter specie is also reported as 8.9% strength increase in cementitious mortar (Park et al, 2010).…”
Section: Mechanical Evaluation Of Cementitious Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Adopting bacteria with spores that activated in the water and oxygen is essential. Another solution is to apply protection immobilized thorough various carrier compounds as silica gel, polyurethane (PU) [118], graphite-nano-platelets (GNP), melamine based microcapsules [119], hydrogel [49], diatomaceous earth [120], light-weightaggregate (LWA) as expanded clay particles Liapor [121][122][123] and immobilized on nano-/micro-additives [124]. ii) Most organisms did not survive in a pH value above 10.…”
Section: Demerits Of Frbcmentioning
confidence: 99%
“…Therefore, a variety of materials are used as carriers to encapsulate microorganisms, such as polyurethane, ,, hydrogel, microcapsule, and other organic polymer materials. Moreover, graphite nanoplatelets (GNPs), iron oxide nanosized particles (IONPs), silica gel, , expanded clay particles, ,, expanded perlite (EP) particles, , ceramsite, calcium sulfo-aluminate cement, recycled aggregate, aerated concrete granules, lightweight aggregates (LWAs), ,, diatomaceous earth (DE), and many other inorganic materials are used as carriers. These carriers can protect microorganisms from the complex environment inside the concrete to a certain extent, prolong the survival time of microorganisms, and improve the self-healing efficiency of concrete cracks in later ages.…”
Section: Introductionmentioning
confidence: 99%